International Transmission of Credit Shocks in an Equilibrium Model with Production Heterogeneity - Yuko Imura; Julia K. Thomas (Bank of Canada, 2015)
Many policy-makers and researchers view the recent financial and real economic crises across North America, Europe and beyond as a global phenomenon. Some have argued that this global recession has a common source: the U.S. financial crisis. This paper investigates the extent to which a credit shock in one country is transmitted to its trade partners. To this end, we develop a quantitative two-country dynamic stochastic general equilibrium model wherein intermediate-good producers face persistent idiosyncratic productivity shocks and occasionally binding collateralized borrowing constraints for investment loans. We find that a negative credit shock to one country induces a sharp contraction in that country's economy, whereas the resulting recession in the economy of its trading partner is quantitatively minor. Transmission through goods trade is limited by the calibrated average trade share, which we find insufficient to deliver a sizable recession abroad. The degree of credit-shock transmission depends on the home bias in international trade and the type of goods countries trade with each other. We show that lower home bias dampens the domestic recession following a credit shock, but it amplifies international transmission. Similarly, when traded goods are less substitutable, the domestic recession is less severe, while real consequences abroad are greater. Our model also predicts that credit shocks cause larger declines in international trade than do productivity shocks. These results shed light on the great trade collapse over 2008-09, suggesting that tightened financial constraints may have been a contributing factor.
Keywords: E22; E32; E44; F41; F44; 330; Business fluctuations and cycles; Economic models; Financial markets; Financial stability; International topics